The mage-fire war - Modesitt, L. E., Jr., 1943- (Modesitt, L. E., Jr., 1943- Saga of Recluce., 2019)
Once again, prejudices against the use of chaos magic force Beltur and his companions to flee their refuge in Axalt. The rulers of nearby Montgren have offered them sanctuary and the opportunity to become the Councilors of the run-down and disintegrating town of Haven. Montegren lacks any mages<U+2015>white or black<U+2015>making this seem like the perfect opportunity to start again. However, Beltur and the others must reinstitute law and order, rebuild parts of the town, deal with brigands<U+2015>and thwart an invading army.